Investigation of a female manifesting Becker muscular dystrophy. - Glass, I A (1992)
Females manifesting Becker muscular dystrophy (BMD) are even more rarely observed than for the allelic condition Duchenne muscular dystrophy. The male proband has typical BMD with greatly raised CK activity and a myopathic muscle biopsy. His mother experienced walking difficulties from 35 years of age and has a myopathy with marked calf hypertrophy, a raised CK, and a myopathic muscle biopsy. Dystrophin analysis was undertaken on both the proband and his mother. Immunoblotting showed a protein of normal size but of reduced abundance in both. Immunocytochemical analysis in the proband indicated that the majority of the fibres showed weak dystrophin labelling and in his mother both dystrophin positive and dystrophin negative fibres were present. Non-random X inactivation at locus DXS255, was observed in DNA isolated from peripheral lymphocytes of the mother. Neither extended multiplex PCR performed on DNA from the proband nor analysis of lymphocyte derived mRNA showed a structural alteration in the dystrophin gene suggesting that an unusual mutation was responsible for BMD in this family.